A hybrid computational intelligence approach for structural damage detection using marine predator algorithm and feedforward neural networks. (August 2021) - Ho, Long Viet; Nguyen, Duong Huong; Mousavi, Mohsen; De Roeck, Guido; Bui-Tien, Thanh; Gandomi, Amir H.; Wahab, Magd Abdel
Highlights: Hybrid feedforward neural networks and marine predator algorithm for structural health monitoring. Superiority of the algorithm is demonstrated through comparison with other algorithms such as PSO, GSA, PSOGSA, and GWO. Application to a simply supported beam, a two-span continuous beam, and a laboratory free-free beam. Abstract: Finite element (FE) based structural health monitoring (SHM) algorithms seek to update structural damage indices through solving an optimisation problem in which the difference between the response of the real structure and a corresponding FE model to some excitation force is minimised. These techniques, therefore, exploit advanced optimisation algorithms to alleviate errors stemming from the lack of information or the use of highly noisy measured responses. This study proposes an effective approach for damage detection by using a recently developed novel swarm intelligence algorithm, i.e. the marine predator algorithm (MPA). In the proposed approach, optimal foraging strategy and marine memory are employed to improve the learning ability of feedforward neural networks. After training, the hybrid feedforward neural networks and marine predator algorithm, MPAFNN, produces the best combination of connection weights and biases. These weights and biases then are re-input to the networks for prediction. Firstly, the classification capability of the proposed algorithm is investigated in comparison with some well-known optimization algorithms such as particle swarm optimization (PSO), gravitational search algorithm (GSA), hybrid particle swarm optimization-gravitational search algorithm (PSOGSA), and grey wolf optimizer (GWO) via four classification benchmark problems. The superior and stable performance of MPAFNN proves its effectiveness. Then, the proposed method is applied for damage identification of three numerical models, i.e. a simply supported beam, a two-span continuous beam, and a laboratory free-free beam by using modal flexibility indices. The obtained results reveal the feasibility of the proposed approach in damage identification not only for different structures with single damage and multiple damage, but also considering noise effect.